Between Asia and empire: infrastructures of encounter in the archive of war. Issue 2 (3rd April 2019) - Attewell, Nadine; Attewell, Wesley
ABSTRACT: In this essay, we stage a conversation about our experiences researching everyday histories of encounter between Asian and Asian diasporic subjects during the Pacific and Vietnam Wars. Through readings of materials from the archives of two empires, Britain and the United States, with bloody records of military intervention in east and south-east Asia, we show how wartime inter-Asian, Afro-Asian, and Asian diasporic geographies of relation overlapped with and animated one another, helping to (re)produce trans-local communities of affinity over space and time even as they also functioned as infrastructures for empire. Throughout, we reflect on the infrastructures – material, institutional, epistemological, affective – that make inter-referencing possible, both for our subjects and, importantly, for ourselves. If our archives resonate, what does this tell us about the trans-imperial durability of the intimate infrastructures we show taking shape in 1940s China and 1960s Vietnam respectively?